Analysis of the Influence of Company Size and Profitability on Company Value - Aliza Maulida Fauzya (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
The purpose of this study is to determine whether company size and profitability will affect firm value. In this study, company size is measured by the total assets owned by the company, while profitability is measured using ROA. The data studied came from the official website of the Indonesia Stock Exchange (BEI), while the object of this study was companies indexed by LQ 45 for the 2016-2019 period. The research hypothesis was tested using multiple linear regression. The results showed that company size and profitability had a positive effect on firm value. This research implies that the company has total assets and profits which have a large effect on the value of the company itself. Therefore, this study contributes to a better visualization for potential investors who will invest in a company by first paying attention to some of the determinants of the value of a company.